Utility assessment among patients of primary angle closure/glaucoma in China: a preliminary study. Issue 7 (10th February 2009) - Sun, X; Zhang, S; Wang, N; Liang, Y; Wang, L; Fan, S; Sun, L
Abstract : Aim: To evaluate utility values among patients of primary angle closure/glaucoma (PAC/G) in a local hospital in China, and the factors influencing the quality of their lives. Methods: A cross-sectional study. Utility values were measured using the time trade-off (TTO) and standard gamble (gamble for blindness) methods. Standard face-to-face interviews were conducted. Results of ophthalmic examinations were recorded. Results: One hundred and six patients were recruited, 16 (15.1%) male and 90 (84.9%) female, mean age 63.21 years (SD 7.46). Fifty-five (50.9%) patients had a history of acute angle closure (AAC). The mean duration from glaucoma diagnosed to the day of interview was 7.69 (3.30) months. All participants underwent laser therapy, and 12 patients (11.3%) also received trabeculectomies. The mean utility value was 0.75 (0.14) (95% CI 0.73 to 0.78) with the TTO technique and 0.80 (0.08) (95% CI 0.78 to 0.81) with the standard gamble (SG) technique. The correlation between the two values was significant (p<0.001). Age, educational status, better best-corrected visual acuity (BCVA), worse BCVA and better visual field had significant effects on the utility values. Patients' self-evaluation of the impact of PAC/G upon their lives correlated with the TTO utility values (p = 0.008) and not with the SG utility values (p = 0.652). Conclusion: The mean TTO utility score of the studied population is 0.75. The utility value is directly dependent on age, the degree of visual function loss and educational status. It is likely that patients find the TTO method easier to comprehend than the SG method.